Scientific bases for the preparation of heterogeneous catalysts : proceedings of the 8th international symposium, Louvain-la-Neuve, Belgium 9-12, 2002 /: proceedings of the 8th international symposium, Louvain-la-Neuve, Belgium 9-12, 2002. ([2014?]) - Unknown
No abstract available